2003
DOI: 10.1046/j.0919-8172.2003.00602.x
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic activity of honey in an experimental bladder cancer implantation model: In vivo and in vitro studies

Abstract: Objectives : The antitumor effect of bee honey against bladder cancer was examined in vitro and in vivo. Methods: Three human bladder cancer cell lines (T24, 253J and RT4) and one murine bladder cancer cell line (MBT-2) were used in these experiments. In an in vitro study, the antitumor activity was assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay, TdTmediated dUTP-biotin nick end labeling (TUNEL) assay, 5-Bromodeoxyuridine (BrdU) labeling index and flowcytometry (FCM). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
109
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(119 citation statements)
references
References 9 publications
4
109
0
6
Order By: Relevance
“…Bladder cancer remains one of the main malignancies that affect the genitourinary tract 37, 38. The main clinical treatment is surgical resection assisted by chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder cancer remains one of the main malignancies that affect the genitourinary tract 37, 38. The main clinical treatment is surgical resection assisted by chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of cell population in G 0 /G 1 phase was also observed in other cancer cell lines after honey or chrysin treatments. Honeyinduced cell growth inhibition through accumulation of cell population in G 1 phase was also observed in T24 bladder cancer cell lines (32). Chrysin-induced G1 arrest in C6 glioma cells has been demonstrated to be caused by increased p21…”
Section: Discussionmentioning
confidence: 88%
“…High phenolic and hydroxylmethylfurfural (HMF) contents of honey resulted in the growth inhibitory effects of cancer cells [30], and flavonoids have been reported to induce cell death of various cancer cell lines [31]. It has previously been reported that a Japanese pure unfractionated honey significantly reduced the proliferation of the human bladder cancer cells, T24 [32]. It has been reported that other type honey shows no significant cytotoxic effect on normal human cell lines [33].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore we hypothesize that acacia honey mediated inhibitory effects of cell growth of PC-3 cells might be due to perturbation in the cell cycle, which may possibly lead to programmed cell death. The antiproliferative effect of honey on human (A375) and murine (B16-F1) melanoma cell lines was found to be mediated by G0/G1 cell cycle arrest and induction of hyperploid progression [22,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation